2016
DOI: 10.3109/17453674.2016.1152855
|View full text |Cite
|
Sign up to set email alerts
|

Increasing wrist fracture rates in children may have major implications for future adult fracture burden

Abstract: Background and purposeChildhood fractures are associated with lower peak bone mass (a determinant of osteoporosis in old age) and higher adult fracture risk. By examining time trends in childhood fracture epidemiology, it may be possible to estimate the vector of fragility fracture risk in the future.Patients and methodsBy using official inpatient and outpatient data from the county of Skåne in Sweden, 1999–2010, we ascertained distal forearm fractures in children aged ≤ 16 years and estimated overall and age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
(43 reference statements)
2
19
0
1
Order By: Relevance
“…Previous studies showed the incidence of distal forearm fractures in children and adolescents has increased. [1315,18] Annual proportion of TULFs in the current study increased from 22.9 patients to 141.6 patients and then decreased to 105.5 patients with year of admission per 100,000 hospital admissions per 2-year period. Our findings emphasize that a multifactorial approach to the prevention of upper limb fractures is necessary if the incidence of these fractures is to be reduced through medical or public health interventions.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies showed the incidence of distal forearm fractures in children and adolescents has increased. [1315,18] Annual proportion of TULFs in the current study increased from 22.9 patients to 141.6 patients and then decreased to 105.5 patients with year of admission per 100,000 hospital admissions per 2-year period. Our findings emphasize that a multifactorial approach to the prevention of upper limb fractures is necessary if the incidence of these fractures is to be reduced through medical or public health interventions.…”
Section: Discussionmentioning
confidence: 53%
“…[ 17 , 18 ] Some studies have shown an increasing incidence of pediatric fractures at specific sites. [ 19 22 ] However, population-based data on overall pattern and epidemiological trends of traumatic fractures (TFs) resulting from falls in children and adolescents are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Different countries with different culture, and daily activities presented with different patterns of fractures. [3][4][5][6][7][8] Some specific fracture sites had an increasing incidence in pediatric patients, 9,10 but data on the patterns and epidemiologic trends of traumatic facial fractures in China are scarce. Compared with facial fractures occurring in adults, traumatic facial fractures in children and adolescents are relatively uncommon.…”
mentioning
confidence: 99%